Investigating quality in Education through the use of an active learning framework : the case of an intervention in the Namibian Environmental Studies curriculum - Jacobs, Nicola Clara (Rhodes University, Faculty of Education, Department of Education, 2015)
The study was conducted to explore the relationship between active learning processes emerging from the use of O'Donoghue's (2001) active learning framework and a series of education quality indicators proposed by Nikel and Lowe (2010). To achieve this aim a professional educational intervention was conducted encouraging the use of this active learning framework in the Namibian Environmental Studies Curriculum, in order to strengthen educational quality within the Environmental Studies Curriculum. The research was conducted in the Windhoek region at the school where I am currently teaching. Four teachers took part in this study, including myself in the role of a participantobserver. The active learning framework was used to guide us in the planning and presentations of environmental learning lessons. The study was conducted within the interpretive paradigm and was qualitative in nature as well as focusing on a quantitative aspect to analyse some of the data (learners' written work). Qualitative data were generated through individual interviews, focus-group discussions, lesson observations and document analysis. The key findings of the study were that: a) prior to the intervention with the active learning framework the teachers who took part in the study did not ask learners to explore environmental issues in the environment or to respond to particular environmental issues; b) active learning processes have the potential to facilitate the exploration of environmental issues in the environment, and responses to particular environmental issues. Active learning also have the potential to strengthen all aspects of education quality indicated in Nikel and Lowe's (2010) quality model, namely effectiveness, efficiency, equity, relevance, responsiveness, reflexivity and sustainability; c) the active learning framework encouraged teachers to use a variety of situated learning approaches, such as the collaborative method, the cooperative method, the problem-solving method and the enquiry method, in order to strengthen the educational quality in Environmental Studies classrooms; and d) teachers find the active learning framework useful as a tool for planning and presenting environmental learning lessons. The findings of the study have the potential to inform curriculum developers, materials developers and educators with an interest in improving education quality through environmental learning processes within the Environmental Studies Curriculum in Namibia. Furthermore, Nikel and Lowe's education quality indicators provided an informative and comprehensive understanding of education quality and provided a useful tool in evaluating and reflecting on education quality as well as my own work as a teacher.
Keywords: Environmental education -- Study and teaching -- Activity programs -- Namibia -- Windhoek; Active learning -- Namibia -- Windhoek; Education -- Evaluation